Bulk-state and single-particle imaging are central to understanding carbon dot photo-physics and elucidating the effects of precursor composition and reaction temperature. (April 2019) - Fathi, Parinaz; Khamo, John S.; Huang, Xuedong; Srivastava, Indrajit; Esch, Mandy B.; Zhang, Kai; Pan, Dipanjan
Abstract: Carbon dots have garnered attention for their strong multi-color luminescence properties and unprecedented biocompatibility. Despite significant progress in the recent past, a fundamental understanding of their photoluminescence and structure-properties relationships, especially at the bulk vs. single-particle level, has not been well established. Here we present a comparative study of bulk- and single-particle properties as a function of precursor composition and reaction temperature. The synthesis and characterization of multicolored inherently functionalized carbon dots were achieved from a variety of carbon sources, and at synthesis temperatures of 150 °C and 200 °C. Solvothermal synthesis at 200 °C led to quantum yields as high as 86%, smaller particle sizes, and a narrowed fluorescence emission, while synthesis at 150 °C resulted in a greater UV–visible absorbance, increase in nanoparticle stability, red-shifted fluorescence, and a greater resistance to bulk photobleaching. These results suggest the potential for synthesis temperature to be utilized as a simple tool for modulating carbon dot photophysical properties. Single-particle imaging resolved that particle brightness was determined by both the instantaneous intensity and the on-time duty cycle. Increasing the synthesis temperature caused an enhancement in blinking frequency, which led to an increase in on-time duty cycle in three out of four precursors. Graphical abstract: Image 1